2013
DOI: 10.1007/s10461-013-0669-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Food and Nutrition Security: Tools and Considerations for Use Among People Living with HIV

Abstract: As an increasing number of countries implement integrated food and nutrition security (FNS) and HIV programs, global stakeholders need clarity on how to best measure FNS at the individual and household level. This paper reviews prominent FNS measurement tools, and describes considerations for interpretation in the context of HIV. There exist a range of FNS measurement tools and many have been adapted for use in HIV-endemic settings. Considerations in selecting appropriate tools include subtypes (food sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 103 publications
(94 reference statements)
0
12
0
3
Order By: Relevance
“…Furthermore, a recent nationally representative study in Canada found that the prevalence of a mental health diagnosis was highest among those reporting food insufficiency (hunger) compared to those reporting poor diet quality (24). Future studies using robust indicators of food insufficiency can help confirm the association between severe food insecurity and symptoms of depression among PLHIV(54). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent nationally representative study in Canada found that the prevalence of a mental health diagnosis was highest among those reporting food insufficiency (hunger) compared to those reporting poor diet quality (24). Future studies using robust indicators of food insufficiency can help confirm the association between severe food insecurity and symptoms of depression among PLHIV(54). …”
Section: Discussionmentioning
confidence: 99%
“…Despite greater household agriculture and livestock ownership in Ziguinchor, the mean IDDS score did not differ between sites. Dietary diversity has been used as a measure of food security [ 36 , 37 ] and lower dietary diversity has been associated with food insecurity among people living with HIV [ 32 ]. This is consistent with our finding that severe food insecurity was associated with lower dietary diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance was to evaluate the food affordability, food accessibility, food utilization and food aid (Pinstrup-Andersen, 2009; Weiser et al., 2012). The study found out that food aid was the most crucial element of food insecurity among the study population (Fielden et al., 2014). Households that were exposed were less likely to receive food (p=0.041) .…”
Section: Discussionmentioning
confidence: 99%